Anabolic steroid consumption among gym-goers in Amman: knowledge, attitudes, and behaviors - Walaa AlKasasbeh; Hatem Shlool; Sajeda Alnaimat (Frontiers Media S.A., 2024)
BackgroundThe use of Anabolic-androgenic steroids (AAS) among gym members has become a significant concern due to their impact on physical training and performance. Research worldwide indicates a notable prevalence of AAS use among athletes and gym attendees, often involving substances that are neither safe nor legal.ObjectivesThis study aims to determine the prevalence of AAS use among gym attendees in Amman, Jordan, and to explore the knowledge, attitudes, and behaviors associated with AAS use.MethodsThe study involved 399 participants from 35 randomly selected gyms in the metropolitan area of Amman, Jordan. A cluster sampling technique was used to select a diverse and representative sample of gym attendees. Data was collected using a self-administered questionnaire that assessed AAS use, knowledge, attitudes, and behavioral factors. Statistical analyses were conducted using chi-square tests to explore the relationships between AAS use and categorical variables, while logistic regression was employed to identify predictors of AAS use.ResultsThe analysis revealed significant associations between AAS use and various factors, including knowledge, attitudes, behavioral factors, and demographic variables such as gender, age, exercise frequency, reasons for exercise, and total exercise duration. The study identified key predictors of AAS use among gym attendees in Amman, highlighting the importance of demographic and behavioral factors.ConclusionThe findings underscore the need for targeted interventions to address misconceptions and promote safer practices among gym-goers in Amman. The study provides critical insights that can guide the development of strategies, policy adjustments, and educational initiatives aimed at reducing AAS misuse and fostering a healthier gym culture in the region.